2012
DOI: 10.4085/1062-6050-47.6.05
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Potassium Concentration and Content Changes After Banana Ingestion in Exercised Men

Abstract: Context: Individuals prone to exercise-associated muscle cramps (EAMCs) are instructed to eat bananas because of their high potassium (K ] p was greater at 60 minutes than at À3 and 5 minutes in the 1-serving condition and was greater at 30 and 60 minutes than at À3 and 5 minutes in the 2-servings condition (P , .05). Percentage change in K þ content was greater only at 30 and 60 minutes postingestion than at baseline in the 2-servings condition (4.4% 6 3.7% and 5.8% 6 2.3% increase, respectively) (P , .05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
(23 reference statements)
0
11
1
7
Order By: Relevance
“…Maintaining electrolyte balance, including sodium and potassium, could be important during or after exercise to relieve cramping. Regarding nutrition, consumption of fruits such as bananas was widely applied by marathon competitors for carbohydrate and potassium supplementation to prevent cramping, but the study demonstrated that potassium was not elevated quickly enough to treat acute EAMCs, especially near the end of a competition [27]. The ORS intervention could be a potential strategy for the amelioration of electrolyte loss for physiological maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining electrolyte balance, including sodium and potassium, could be important during or after exercise to relieve cramping. Regarding nutrition, consumption of fruits such as bananas was widely applied by marathon competitors for carbohydrate and potassium supplementation to prevent cramping, but the study demonstrated that potassium was not elevated quickly enough to treat acute EAMCs, especially near the end of a competition [27]. The ORS intervention could be a potential strategy for the amelioration of electrolyte loss for physiological maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency so that it will cause fatigue [3]. Provision of supplements containing potassium is usually given in the form of natural supplements such as bananas [4].…”
Section: Analysis Of Reduction Fatigue Levels Of Construction Workersmentioning
confidence: 99%
“…Giving carbohydrates of 30-60 grams/hour is able to maintain glucose levels and can maintain the level of carbohydrate burning in the body so that the occurrence of fatigue is inhibited up to 30-60 minutes [16]. Glucose formed will be stored in the bloodstream as blood glucose and as energy reserves in the form of glycogen in the liver and muscles [4].…”
Section: Analysis Of Reduction Fatigue Levels Of Construction Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Berdasarkan studi lain menyebutkan mengkonsumi pisang sebanyak 150 gram dapat meningkatkan kadar kalium darah 30-60 menit setelah dicerna, dan dapat meningkatkan kadar glukosa darah 15, 30, dan 60 menit setelah dicerna sehingga berpotensi mencegah kram otot akibat olahraga. 16 Pisang (Musa paradisiaca) merupakan buah yang mengandung sumber karbohidrat, mineral serta vitamin B6 dan vitamin C yang tinggi. 17,18 Pisang merupakan buah yang teksturnya lunak dan mudah dicerna oleh tubuh.…”
Section: Pendahuluanunclassified